(untitled) (Journal of Oriental Studies, 2016)
In this article, we analyze the meaning of the linguacultural unit, the scope of its use, types, and its role in the creation of figurative language in the world, its research and the theoretical foundations of its translation. Any idioms, set phrases, proverbs and sayings, winged words, itc.arenot the linguacultural unit. Determination of linguaculture unit in the language is not easy task. To do this you need to understand that linguacultural unit is a measure of the national language features.